Factors influencing decomposition of H2O2 over supported Pd catalyst in aqueous medium - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Journal of Molecular Catalysis A-Chemical, 2006)
Since H2O2 decomposition can result in selectivity/yield loss in the direct H2O2 synthesis process from H-2 and O-2 over supported Pd catalysts, it is important to have an enhanced understanding about the factors affecting the H2O2 decomposition reaction. Herein, detailed studies have been undertaken to investigate the influence of different factors, such as (a) nature and concentration of acid in reaction medium, (b) nature and concentration of halide in presence and absence of acid in reaction medium, (c) pretreatment procedures and (d) catalyst modification by incorporation of different halides, on the H2O2 decomposition reaction over a 5% Pd/C catalyst in aqueous medium at 25 degrees C. This study has shown that the H2O2 decomposition activity is profoundly influenced by all the above factors. The effectiveness of the acids in suppressing the H2O2 decomposition activity decreased in the following order: hydroiodic acid > hydrobromic acid > hydrochloric acid >> acetic acid > phosphoric acid > sulfuric acid > perchloric acid. The ability of the acid to decrease the H2O2 decomposition activity was found to very strongly depend on the nature of its associated anion. Halides, such as iodide, bromide and chloride were particularly effective in suppressing the H2O2 decomposition activity. Oxidation pretreatment of the catalyst was found to strongly suppress its H2O2 decomposition activity, while a reduction treatment was found to promote its activity. A gradual decrease in the H2O2 decomposition activity of the catalyst was observed with each successive usage due to in situ sub-surface oxidation of Pd by H2O2. Halide incorporation either via the reaction medium or prior catalyst modification had a similar qualitative effect on the H2O2 decomposition activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acid; H2O2 decomposition; H2O2 synthesis; halides; Pd catalysts; pretreatment

Formation from direct oxidation of H-2 and destruction by decomposition/hydrogenation of H2O2 over Pd/C catalyst in aqueous medium containing different acids and halide anions - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Applied Catalysis A-General, 2007)
Direct oxidation of H-2 by O-2 to H2O2 and decomposition/hydrogenation of H2O2 (at 27 degrees C and atmospheric pressure) over Pd/C catalyst in an aqueous acidic reaction medium have been thoroughly investigated using different mineral acids (viz. 0.1 N H2SO4, H3PO4, H3BO3, HNO3, HCl, HBr or HI) and/or halide anions (viz. F-, Cl-, Br- or I-), covering their wide concentration range (0-24 mmol/dm(3)), in the reaction medium. In the absence of any externally added halide, appreciable H2O2 formation in the H2 oxidation occurred only when the medium contained HCl. However, the rates of H2O2 decomposition and hydrogenation are greatly reduced because of the presence of any acid; the influence on the H2O2 decomposition was, however, much larger for the halo acids. In the presence of acid (0.1 N H3PO4 or H2SO4), the H-2-to-H2O2 formation reaction is greatly enhanced by the externally added halide anions up to their optimum concentrations. However, above the optimum halide anion concentration, it is inhibited more than the H-2-to-water formation (parallel) reaction, causing a decrease in both the H2O2 yield and selectivity. Whereas, the H-2 conversion and H2O2 destruction activities of the catalyst are decreased continuously with increasing the halide anion (except F-) concentration. Among the halides, chloride is the best halide promoter for Pd/C catalyst in the H-2-to-H2O2 oxidation. At the optimum Cl-concentration (5.4 mmol/dm(3)), both the H-2 conversion and H2O2 yield are passed through a maximum and the H2O2 decomposition is greatly inhibited with increasing the phosphoric acid concentration. In the absence of either the chloride anions or the acid (or both) in the reaction medium, only a little or no H2O2 is formed in the H-2 oxidation and also the rate of H2O2 destruction is very fast, particularly in the presence of H-2; the rapid destruction of H2O2 is mainly due to its decomposition rather than its hydrogenation. The best H-2-to-H2O2 oxidation results are obtained at the optimum concentrations of both the acid and halide anions. In the presence of acid and chloride (or bromide) promoter, the H2O2 hydrogenation dominates the H2O2 destruction and hence the net H2O2 formation is mainly controlled by the H2O2 hydrogenation. (c) 2006 Published by Elsevier B.V.
Keywords: H2O2 decomposition; H2O2 hydrogenation; halide anion promoters; Hydrogen peroxide; oxidation of H-2-to-H2O2; Pd/C catalyst

Factors influencing the in situ generation of hydrogen peroxide from the reduction of oxygen by hydroxylamine from hydroxylammonium sulfate over Pd/alumina - Choudhary, Vasant R.; Jana, Prabhas (Applied Catalysis A-General, 2008)
Influence of the concentration of bromide (KBr) promoter, reaction period, temperature, catalyst loading and initial concentration of hydroxylammonium sulfate on the formation of H2O2 due to the reaction between hydroxylamine from the hydroxylammonium salt and molecular oxygen over Pd (1 wt%)/Al2O3 catalyst in a neutral aqueous medium at close to the ambient conditions has been investigated. Effect of pH and temperature on the destruction of H2O2, Occurring in the consecutive reactions, over the catalyst in the presence or absence of bromide promoter and hydroxylamine has also been studied. In the absence of O-2, the conversion of hydroxylamine by its decomposition over the catalyst increases sharply with increasing the pH, particularly above the pH of 7.0; at or below the pH of 7.0, it is quite small. The H2O2 destruction increases markedly with increasing the pH of medium and reaction temperature but it is found to decrease in the presence of hydroxylamine. For the highest net H2O2 formation, not only the optimum pH (7.0) of reaction medium but also the optimum other reaction conditions (viz. bromide promoter concentration, reaction period, temperature or catalyst loading) are necessary. The reaction path and mechanism for the generation of H2O2 have also been suggested. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: H2O2 destruction; Hydrogen peroxide; hydroxylamine; Hydroxylammonium sulfate; Pd/Al2O3 catalyst; reduction of O-2

FeCl3/Montmorillonite K10 as an efficient catalyst for solvent-free aza-Michael reaction between amine and alpha,beta-unsaturated compounds - Choudhary, Vasant R.; Dumbre, Deepa K.; Patil, S. K. (RSC Advances, 2012)
A highly efficient, inexpensive and greener protocol for aza-Michael addition reaction of different aromatic and aliphatic/cyclic amines to alpha,beta-unsaturated compounds using a FeCl3/MontK10 catalyst under solvent-free conditions has been developed. The Michael addition products are obtained in good to excellent yields. The catalyst was insensitive to moisture and it also showed excellent reusability in the reaction. Its high activity is attributed mostly to redox properties of FeCl3.